Knockdown of asparagine synthetase A renders trypanosoma brucei auxotrophic to asparagine - Loureiro, Ines; Faria, Joana; Clayton, Christine; Ribeiro, Sandra Macedo; Roy, Nilanjan; Santarém, Nuno; Tavares, Joana; Cordeiro-da-Silva, Anabela (PLoS neglected tropical diseases, 2013)
Asparagine synthetase (AS) catalyzes the ATP-dependent conversion of aspartate into asparagine using ammonia or glutamine as nitrogen source. There are two distinct types of AS, asparagine synthetase A (AS-A), known as strictly ammonia-dependent, and asparagine synthetase B (AS-B), which can use either ammonia or glutamine. The absence of AS-A in humans, and its presence in trypanosomes, suggested AS-A as a potential drug target that deserved further investigation. We report the presence of functional AS-A in Trypanosoma cruzi (TcAS-A) and Trypanosoma brucei (TbAS-A): the purified enzymes convert L-aspartate into L-asparagine in the presence of ATP, ammonia and Mg2+. TcAS-A and TbAS-A use preferentially ammonia as a nitrogen donor, but surprisingly, can also use glutamine, a characteristic so far never described for any AS-A. TbAS-A knockdown by RNAi didn't affect in vitro growth of bloodstream forms of the parasite. However, growth was significantly impaired when TbAS-A knockdown parasites were cultured in medium with reduced levels of asparagine. As expected, mice infections with induced and non-induced T. brucei RNAi clones were similar to those from wild-type parasites. However, when induced T. brucei RNAi clones were injected in mice undergoing asparaginase treatment, which depletes blood asparagine, the mice exhibited lower parasitemia and a prolonged survival in comparison to similarly-treated mice infected with control parasites. Our results show that TbAS-A can be important under in vivo conditions when asparagine is limiting, but is unlikely to be suitable as a drug target.
Gesehen am 08.06.2021